'High-Commission'd' Fancy in the Poetry of Leigh Hunt, John Keats, John Hamilton Reynolds, and John Clare. (April 2013) - White, Adam
Abstract : Fancy has traditionally taken second place to imagination in critical accounts of creative categories and faculties in the Romantic period. This essay argues that fancy is in fact accorded a special privilege in the work of Hunt, Keats, Reynolds, and Clare, and that their poetry can be seen to complicate claims made by William Wordsworth and Samuel Taylor Coleridge for imagination's greater scope and power.